2018
DOI: 10.1021/acs.jmedchem.7b01862
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of 4-Quinoline Carboxylic Acids as Inhibitors of Dihydroorotate Dehydrogenase

Abstract: We pursued a structure-guided approach toward the development of improved dihydroorotate dehydrogenase (DHODH) inhibitors with the goal of forming new interactions between DHODH and the brequinar class of inhibitors. Two potential residues, T63 and Y356, suitable for novel H-bonding interactions, were identified in the brequinar-binding pocket. Analogues were designed to maintain the essential pharmacophore and form new electrostatic interactions through strategically positioned H-bond accepting groups. This e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 55 publications
(124 reference statements)
3
36
0
Order By: Relevance
“…Elemental analysis (% CHN) was run by combustion analysis through an outsourced service (Medac Ltd, Surrey, UK). Commercial compounds were used as received; 2-(4-bromophenyl)quinoline-4-carboxylic acid ( 3a ) [20] and 2-(4-bromophenyl)-6-methoxyquinoline-4-carboxylic acid ( 3b ) [21] were accessed via the standard Pfitzinger reaction protocol [8].…”
Section: Methodsmentioning
confidence: 99%
“…Elemental analysis (% CHN) was run by combustion analysis through an outsourced service (Medac Ltd, Surrey, UK). Commercial compounds were used as received; 2-(4-bromophenyl)quinoline-4-carboxylic acid ( 3a ) [20] and 2-(4-bromophenyl)-6-methoxyquinoline-4-carboxylic acid ( 3b ) [21] were accessed via the standard Pfitzinger reaction protocol [8].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a series of hDHODH inhibitors were discovered by scaffold-hopping strategy or structural modification based on previous reported lead compounds [16,17] In our instance, the active compounds were selected based on in vitro screening. Our screening discovered a novel class of human DHODH inhibitors, which have a 6-isopropyl-1,5,6,7-tetrahydro-4Hbenzo[d] [1,2,3]triazol-4-one scaffold.…”
Section: A Novel Class Of Potent Inhibitors Of Human Dhodhmentioning
confidence: 99%
“… 41 reported that inhibition of DHODH can overcome differentiation blockade in AML. There were also promising DHODH inhibitors in the preclinical stage such as S312 ( 8 ) which is reported to display broad-spectrum antiviral activities against various RNA viruses including influenza A virus, Zika virus, Ebola virus, and particularly against SARS-CoV-2 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 . Besides, the new roles of DHODH in various cancer types were also uncovered in recent years 50 , 51 , 52 , 53 , 54 , 55 .…”
Section: Introductionmentioning
confidence: 99%